Diaphragm motor responses to phrenic nerve stimulation in ALS: Surface and needle recordings. Issue 2 (February 2018) - de Carvalho, Mamede; Pinto, Susana; Swash, Michael
Highlights: Phenic nerve (PN) motor response can successfully be recorded by surface or needle electrodes in ALS. PN amplitude/area recorded by surface electrodes is highly correlated with respiratory function. PN amplitude/area recorded by surface electrodes is closely associated with diaphragm innervation. Abstract: Objective: In studies of phrenic nerve (PN) conduction in amyotrophic lateral sclerosis (ALS) both motor response amplitude and latency have been reported as abnormal. However, correlation with diaphragm motor unit loss, and with diaphragmatic function has not been fully evaluated. Methods: We studied 83 patients with ALS, and 21 patients referred with clinically suspected phrenic nerve lesions whose studies were normal. PN responses elicited by percutaneous electrical stimulation in the neck were recorded using superficial electrodes placed at the surface markings of the diaphragm on the chest wall, and a concentric needle electrode inserted into the diaphragmatic costal fibres. Electromyography of diaphragm was performed to analyse motor unit morphology and recruitment. Results: The 21 controls and 83 ALS patients were matched for age. In controls, the only significant correlation between surface and needle recording was for negative-peak amplitude (p = 0.03). In ALS patients, amplitudes and negative-peak area were highly correlated (p < 0.001), as were PN motor latencies (p = 0.002). Forced vital capacity (FVC) was highly correlated with both amplitude (p < 0.001) and PN latency (p < 0.02), whichever electrode was used. PN amplitude recording with needle electrode was consistent with EMG findings in the diaphragm. Conclusion: In ALS, PN motor amplitude/area and latency measurements recorded by surface electrodes are highly correlated with needle EMG findings in the diaphragm. CMAP amplitude/area measurements showed high correlation with FVC. Significance: In ALS, amplitude/area of the motor PN response, recorded by surface or needle electrodes, correlates with dysfunction of the diaphragm.